Nonpharmacological management of neonatal abstinence syndrome: a review of the literature. (19th May 2019) - Ryan, Gareth; Dooley, Joe; Gerber Finn, Lianne; Kelly, Len
Abstract: Background: Infants with neonatal abstinence syndrome (NAS) experience withdrawal that occurs as a result of termination of placental opioid supply following delivery. Common symptoms include restlessness, tremors, agitation and gastrointestinal disturbances. Severe NAS is often treated using opioids and/or sedatives. Although commonly employed effectively in neonatal care, there is a lack of published information regarding nonpharmacological management of the NAS infant. Objective: The purpose of this review was to summarize the current literature on nonpharmacological management of NAS. Methods: A literature search of Medline and EMBASE was performed for articles published between 2000 and June 2107. Results: Nonpharmacological management encompasses "environmental control", "feeding methods", "social integration", "soothing techniques" and "therapeutic modalities". Several interventions, including: breastfeeding, swaddling, rooming-in, environmental control and skin to skin contact have proven to be effective in managing NAS and should be incorporated into standard of care for this population (Level I–III Evidence). These interventions can be effective when offered in combination with pharmacological therapy, or as stand-alone therapy for less severe cases of NAS (Finnegan score <8). Conclusions: Given the increasing body of evidence on its efficacy and ease of implementation, nonpharmacological treatment should universally be incorporated into standard of care for NAS.